2000
DOI: 10.1046/j.1460-9568.2000.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole inhibits the persistent sodium current in mammalian CNS neurons

Abstract: The effects of 0.1-100 microM riluzole, a neuroprotective agent with anticonvulsant properties, were studied on neurons from rat brain cortex. Patch-clamp whole-cell recordings in voltage-clamp mode were performed on thin slices to examine the effects of the drug on a noninactivating (persistent) Na+ current (INa,p). INa,p was selected because it enhances neuronal excitability near firing threshold, which makes it a potential target for anticonvulsant drugs. When added to the external solution, riluzole dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
258
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 349 publications
(292 citation statements)
references
References 43 publications
31
258
1
2
Order By: Relevance
“…When stress-related glutamatergic dysregulation results in excessive glutamate accumulation in the synapse, glutamatergic neurotoxicity or "excitotoxicity," culminating in neuronal death, has been observed (e.g., 9,10). Riluzole has a complex mechanism of action, including: (1) inhibition of voltage-dependent sodium channels in central nervous system (CNS) neurons (11,12); (2) inhibition of excitotoxic injury (13); (3) increased glutamate reuptake (14); (4) stimulation of growth factor synthesis, including brain-derived neurotrophic factor (BDNF) (15,16); (5) promotion of neuritogenesis, neurite branching, and neurite outgrowth (17); and (6) enhancement of hippocampal AMPA receptor subunit (GluR1 and GluR2) expression (18).…”
Section: Introductionmentioning
confidence: 99%
“…When stress-related glutamatergic dysregulation results in excessive glutamate accumulation in the synapse, glutamatergic neurotoxicity or "excitotoxicity," culminating in neuronal death, has been observed (e.g., 9,10). Riluzole has a complex mechanism of action, including: (1) inhibition of voltage-dependent sodium channels in central nervous system (CNS) neurons (11,12); (2) inhibition of excitotoxic injury (13); (3) increased glutamate reuptake (14); (4) stimulation of growth factor synthesis, including brain-derived neurotrophic factor (BDNF) (15,16); (5) promotion of neuritogenesis, neurite branching, and neurite outgrowth (17); and (6) enhancement of hippocampal AMPA receptor subunit (GluR1 and GluR2) expression (18).…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanism of action involves primary inhibition of VGSC but also reduction of glutamate release [32]. It inhibited persistent sodium current in dose-dependent manner with EC 50 of 2 M while tested in rat brain neurons [32]. Other studies conducted in bovine adrenal chromaffin cells showed blockade of Na + channels by riluzole in concentration-dependent manner with IC 50 =5.3 μM and binding to the veratridine site 2 of channels.…”
Section: Riluzolementioning
confidence: 99%
“…As a result, injury of demyelinated axons in spinal cord is likely to occur [17]. Persistent sodium current may also constitute an important factor contributing to neuronal damage in Amyotrophic Lateral Sclerosis (ALS) [32]. It is worth to mention that multiple sclerosis (MS), a prototypical white matter disorder is not only neuroinflammatory condition but may be also caused by mitochondrial dysfunction and its molecular mechanism of tissue damage is similar to that of hypoxic CNS injury.…”
Section: Neuronal Cell Damage (Neurodegeneration)mentioning
confidence: 99%
See 2 more Smart Citations